Carboxyl-functionalized derivatives of carboxymethyl cellulose: towards advanced biomedical applications. (3rd July 2019) - Pettignano, Asja; Charlot, Aurélia; Fleury, Etienne
Abstract: Carboxymethyl cellulose (CMC) has attracted considerable scientific attention, thanks to its enhanced water solubility and wide range of possible chemical reactions. In the present review, we attempt to summarize the current knowledge on chemical modifications of CMC, focusing specifically on the derivatization of its carboxyl functions, through "grafting onto" strategies. CMC derivatives, obtained by grafting of small molecules and/or polymers, can be engineered as peculiar assembled architectures ( e.g., conjugates, nanoparticles, hydrogels), particularly suitable for the development of drug delivery systems or scaffolds for tissue engineering. The potential of the resulting CMC derivatives in biomedical applications is, therefore, discussed in detail.